Study of acoustic emission under cyclic loading of dissimilar welded joints of 12kh18n10t and grade 20 steel - Barat, V.A.; Marchenkov, A.Yu.; Poroykov, A.Yu.; Lepsheev, E.A.; Pankina, A.A.; Lavrik, N.V. (Edelweiss Applied Science and Technology, 2025)
The paper is devoted to the study of acoustic emission (AE) under cyclic loading of dissimilar welded joints. The object of the study is carbide and decarburized diffusion interlayers that are formed during the welding of pearlitic and austenitic steels, as well as during the subsequent operation of such dissimilar joints under high temperatures. The paper presents the results of an experimental study on cyclic loading of samples of dissimilar welded joints with the registration of AE data and measurement of local deformation fields using the digital image correlation (DIC) method. Loading was carried out in the elastic region at a stress close to the operational values. Analysis of the deformation distribution fields over the surface of the samples showed that welded joints with diffusion interlayers have increased deformation values in the interlayer zone. According to the values of the AE parameters, the level of activity and amplitudes of AE hits for samples with diffusion interlayers are higher than in defect-free samples.